1082 Offsprings Autistic Behaviors Modify The Relationships Between Maternal Peritraumatic Distress And Sleep Disturbance Following Trauma Exposure. (27th May 2020) - Chanko, N; Williams, N; Jean-Louis, G; Casimir, G; Blanc, J
Abstract: Introduction: Neurodevelopmental impairments may alter parents' sleep and add tremendous stress to their families' routine. This study examined the relationship between peritraumatic distress, and sleep disturbances among mothers who were exposed to the 2010 Haitian earthquake during pregnancy and whether this relationship is moderated by offspring's autistic behaviors. Methods: Sample includes 361 mother-offspring dyads [mean (SD) age= 27.31 (5.93); 3.1/2(3.88)] who survived the 2010 earthquake in Haiti. Maternal data were collected 3 years following the event via the Earthquake Experience Questionnaire (EEQ), the Peritraumatic Distress Inventory (PDI), and the sleep items of the PTSD Checklist (PCL-S) (such as trouble falling or staying asleep, and repeated disturbed dreams in response to the disaster exposure). Child-related data were obtained from maternal completion of the Echelle d' Evaluation des Comportements Autistiques Revisee (ECAR) (Autistic Behaviors Scale Revised). Pearson Correlations, multilinear regression and interaction effect analyses were conducted to explore the association between peritraumatic distress, offspring's autistic behaviors and sleep disturbance among the participants. Results: 10.7% of mothers were caught under rubble or were seriously injured during the event. Three years later, 56.83% and 52.9% of them had consequent disturbed sleep and nightmares, respectively. Maternal sleep disturbance correlated positively with peritraumatic distress (r=.38, p=.01) and offspring autistic behaviors (r=.13, p=.05). As hypothesized, adjusting for covariates, peritramatic distress was the strongest predictor of maternal sleep disturbance (B=.310, p<.001). The relationship between maternal peritraumatic distress and sleep disturbance was modified by offspring autistic behaviors (B=.138, p= .015). Conclusion: This is the first study to document the prolonged effect of peritraumatic distress during the 2010 Haitian earthquake on mother's sleep disturbance and whether this relationship is moderated by offspring autistic behaviors. The findings support the importance of a sleep component in maternal and child health in disaster preparedness program. Support: This study was supported by funding from the NIH: T32HL129953